Effect of Monetary Policy on Foreign Direct Investment (FDI) inflows in East African Countries: The Moderating Impact of Institutional Quality - Masengesho, Esther Josiane; Dada, Samuel; Ogboi, Charles (Archives of Business Research, 2025)
The majority of developing countries have heavily relied on foreign direct investment (FDI) inflows over the past years due to the gap between domestic savings and investment. Studies on the interactive effect of monetary policy and institutional quality (IQ) on FDI inflows are still scanty in East African countries. This study examined the effect of monetary policy (monetary policy rate (MPR), exchange rate (ER), reserve requirements (RR)) on FDI inflows in East African Countries with a special focus on the moderating impact of institutional quality. A fixed effect model was applied to analyse panel data spanning from 2003 to 2022. The results showed that incorporating institutional quality into the relationship between monetary policy and FDI inflows marginally improves the model's explanatory power from 56 percent to 57 percent with the interaction of IQ and monetary policy variables suggesting that institutional factors contribute to understanding FDI dynamics. The findings revealed a positive relationship between, IQ and MPR-IQ interaction and FDI inflows, though it was not strong. The results further showed a negative but weak relationship between ER-IQ interaction and FDI inflows. Thus, it is concluded that IQ slightly mitigates the negative impact of MPR on FDI, suggesting that strong institutions create a stable environment that offsets the deterrent effect of higher interest rates. Additionally, though IQ enhances stability, exchange rate fluctuations continue to undermine investor confidence. It is therefore recommended that Policymakers consider a holistic approach, focusing on structural reforms and stable macroeconomic policies to boost investor confidence and attract FDI.